Research and analysis of testing nonlinear overvoltage limiters for high-voltage electrical networks - Bunko, V.; Darmoris, P.; Kondrat, O. (Energy and Automation, 2025)
Research and analysis of nonlinear surge arresters (NSAs) for high-voltage electrical networks is a key process for assessing their effectiveness, reliability, and compliance with standards, which includes: determining NSA characteristics, conducting laboratory and field tests, simulating their operation, analyzing the results, and comparing them with regulatory requirements to ensure the protection of networks from overvoltages.The paper provides a detailed analysis of the testing of AZBD series surge arresters, as well as a study of the surge arrester for a 220 kV high-voltage electrical network of the type OPN-P-220/158/10/2 surge arrester with residual voltage values of 510 kV and 574 kV at a lightning impulse current of 8/20 μs with amplitudes of 10 kA and 20 kA, respectively, and 402 kV and 419 kV at a switching current pulse of 30/60 μs with an amplitude of 500 A and 1000 A, respectively.This article analyzes the testing of surge arresters with short-circuit currents, describes the charge transfer characteristics and energy capacity of surge arresters, presents new tests in accordance with DCU EN 60099-4:2016, and verifies the characteristics of surge arresters after applying bending loads and testing for resistance to environmental influences. A brief description of the structural and basic electrical diagram of the test setup used in the laboratory of electrical installations and power supply systems for testing surge arresters, valve arresters, vitelline discs, and spark gaps of various voltage classes is provided.    The volt-ampere characteristics of the surge arrester, the dependence of the residual voltage on the impulse current, and the dependence of the leakage current on the alternating voltage were constructed. Additional graphs were also constructed for the OPN-P-220/158/10/2 surge arrester, an approximation graph (U = a·Ib) with the obtained equation, a graph of dynamic resistance R = U/I as a function of current, and the dependence of residual voltage on the conditional pulse energy. These graphs together provide a complete picture. In particular, the approximation describes the general mathematical relationship; the dynamic resistance R(I) shows the effectiveness of the limiter; the relationship between the residual voltage and energy U(E) allows us to evaluate the behavior under pulses of different nature. Key words: electrical networks, nonlinear surge arresters, lightning discharge, impulse current, residual voltage, pulses